RESEARCH IN ENGINEERING-GEOLOGICAL CHARACTERISTICS OF FOREST SOILS OF THE CITY OF KYZYLORDA - Budikova Aigul Moldashevna; Kamalova Nazgul Nurlankyzy (Scientific Journal of Pedagogy and Economics, 2021)
The article analyzes the problem of studying loess rocks. The objects of study in this work were foundations composed of soft soils. In engineering-geological assessment of loess deposits, the conditions of occurrence of loess rocks are of great importance. The research was carried out on the territory of Kyzylorda, where the total thickness of the subsidence layer and overlying technogenic deposits reaches 5-7m. The processes studied in the work - long-term sedimentation of subsidence soil, as well as fluctuations in the level of groundwater that affect it, are characteristic of many cities. So on 20% of the territory of Kazakhstan there are peat deposits, and changes in the level of groundwater are one of the main factors that have a negative impact on foundations, underground structures and foundations in cities. The obtained calculation methods, monitoring data, constructive solutions of underground utilities in loess territories can be used in similar engineering and geological conditions, which will increase the reliability of these structures, reduce the cost of their construction and operation